Ministério Público resolutivo e o tratamento adequado dos litígios estruturais - Daher, Lenna Luciana Nunes (2019)
This research is aimed at discussing the role of the Public Prosecution for the proper treatment of structural litigation. The theoretical framework is the access to Justice Movement, understood as the right and fundamental guarantee of access to all legitimate means - jurisdictional and extra-jurisdictional - of protection and of rights implementation. Structural litigation is related to constitutional values which have not been consolidated, and demands, for its solution, the reform of bureaucratic and social structures through the creation or correction of public policies. The study points out some problems faced by adjudication to present effective responses to this kind of complex and multipolar conflicts. Consensual methods of dispute resolution are presented as important instruments to contribute to the production of effective results for structural change. The hypothesis defended is that the Public Prosecution, in view of its role as a guarantee of access to Justice and as a social transformation agent in order to consolidate the founding values of the democratic State of law, has the essential requirements to act as the protagonist in obtaining consensus for the extra-jurisdictional solution of the structural litigation. However the resolutive adjustment must be lead by parameters, extracted from the constitution, that promote the legitimacy and effectiveness of the consensual solution. In the conclusion of this research some measures are proposed in order to enhance the organic and functional management of the Public Prosecution, for the treatment of complex situations, such as structural conflicts.